The Influence of Emo Demo on Mother’s Knowledge and Attitudes in Providing Infant Feeding - Kirana Ayu Palupi; Irawan, Andi Muh Asrul; Yusuf, Andi Mukramin; Rahmawati, Lusi Anindia; Umami, Zakia (Media Publikasi Cendekia Indonesia, 2024)
Children under two years old are a critical period in child development, characterized by rapid growth and development. One nutritional issue, stunting, can arise from inappropriate feeding practices and leads to impaired brain development, intelligence, physical growth, and metabolic function. To address this, we implemented Emotional Demonstration education on baby and child feeding schedules for young mothers. This study aimed to analyze the impact of Emotional Demonstration education on mothers’ knowledge and attitudes regarding toddler feeding practices at Dahlia Posyandu, Pabuaran Village, Bogor Regency. A Pre-Experimental One Group Pre-Test Post-Test design was employed involving 32 young women from the Bojonggede Community Health Center. Data were collected through pre-test and post-test questionnaires, analyzed using the Wilcoxon test. Results indicate a significant improvement in mothers’ knowledge following Emotional Demonstration education. However, no significant change was observed in their attitudes. In conclusion, Emotional Demonstration education effectively enhances maternal knowledge about baby and child feeding schedules but does not influence their attitudes